Marketing monitoring of biotechnological internet resources and internet market of ecology related biotechnological developments. - E. A. Demcheva; M. V. Tsarikovskaya; E. I. Khabarova; V. B. Lukmanov (Тонкие химические технологии)
The development grade of biotechnological branch is varies significantly according to every different branch direction. One of such direction is the market of ecology related biotechnological developments, which was monitored using marketing research in 2002- 2006.